IMPLEMENTASI SANITASI TOTAL BERBASIS MASYARAKAT (STBM) BERSAMA PROGRAM KKN DI DESA TARO GIANYAR - Dwipayanti N.M.U; Sutiari N. K. (Buletin Udayana Mengabdi, 2013)
One target of MDG 2015 is to reduce by half the pulation without access to water and basic sanitation. The HealthMinistry of Indonesia has an effort to increase basic sanitation access through National Strategy of CommunityBased Total Sanitation (STBM) started from 2008. According to data from the local primary health care (Puskesmas)Tegalalang II, the sanitation coverage in some area of Taro Village are low. For that reason, in cooperation withHealth Agency of Gianyar, Puskesmas Tegalalang II, the activity of KKN in Taro Village was integrated with STBMprogram focusing on hygiene behavior change in terms of stop open defecation without any subsidy provided.The preparation was started with training of STBM facilitator participated by KKN students. It was then followedby triggering of stop open defecation as well as promoting hand washing with soap in Banjar Tebuana, Taro,Gianyar. The trigering and promoting activities were conducted through participatory rural appraisal (PRA) methodthat utilising Participatory Hygiene and Sanitation Transformation (PHAST). In order to have baseline data insanitation, then verification of sanitation facilities already built in the village was carried out. From the trigeringprocess only 3 families that commited to build toilet. The community always consider that poverty as the mainreason why they could not afford for a toilet. From the verification result, only 21,21% families that have toilet, andonly 38% of those toilet that categorised as hygiene toilet. Moreover, only 55,55% of families that have facilitiesfor washing hand with soap.Based on the trigering and verification result, it is recommended that facilitating thisvillage to rapidly reduce the number of families without access to basic sanitation is very important to continue.The role of sanitarian at Puskesmas cooperated with village government to facilitate their community in pursingbehavior change is also very crucial.